Negative electrode active material, its preparation method and use
By coating silicon-oxygen compound particles with a defect-reduced carbon film layer, the negative electrode active material addresses issues of cycle stability and high-temperature performance in lithium-ion batteries, resulting in improved battery efficiency and safety.
Patent Information
- Application Number
- JP2024551553
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-02
- Filing Date
- 2023-02-24
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2043-02-24
AI Technical Summary
Silicon-oxygen compound negative electrode active materials for secondary batteries face issues such as poor cycle characteristics, irreversible lithium loss due to side reactions, low ionic and electron conductivity, and instability at high temperatures, which affect battery performance and safety.
A negative electrode active material is developed with a silicon-based material core containing a silicon-oxygen compound, coated with a carbon film layer to enhance stability and conductivity. The carbon film layer is designed to minimize defects, improving interface stability and cycle life while reducing expansion and gas generation.
The proposed solution achieves improved cycle stability, high temperature characteristics, reduced expansion, and low gas generation, thereby enhancing the performance and safety of lithium-ion batteries.
Smart Images

Figure 2025508921000001_ABST
Abstract
Description
[Technical field]
[0001] The present application relates to the field of batteries, and in particular to a negative electrode active material for secondary batteries, a preparation method thereof, an electrode, and a battery. [Background technology]
[0002] Currently, there are three main types of silicon anode active materials being developed: the first type is a composite material of silicon alone (including nanosilicon, porous silicon, amorphous silicon, etc.) and carbon material, the second type is an alloy material composed of silicon and other metals (iron, manganese, nickel, chromium, cadmium, tin, copper, etc.) and nonmetallic components (carbon, nitrogen, phosphorus, boron, etc.), and the third type is a composite material of silicon oxide compounds and their carbon materials. However, for the first and second types of materials, due to many factors related to the silicon alone itself, the obtained electrode materials have poor cycle characteristics, are easily pulverized, and are easily separated from the current collector.
[0003] Since silicon-oxygen compounds contain more inactive materials, their capacity is lower than that of silicon-only negative electrode active materials; however, at the same time, the presence of these inactive components effectively restrains the expansion of silicon during the cycling process through the inactive phase, which has obvious advantages in terms of cycle stability.
[0004] Silicon-oxygen compounds also have their own problems. When these materials first intercalate lithium, many side reactions with the electrolyte often result in the formation of a thick SEI film on the particle surface, and irreversible lithium desorption materials such as lithium silicate and lithium oxide are formed inside the particles, resulting in irreversible loss of lithium ions in the battery. The above two irreversible reactions result in low initial coulombic efficiency of lithium-ion batteries containing silicon-oxygen compound anodes, limiting the improvement of the full cell energy density. In addition, silicon-oxygen compounds also have problems such as low ionic and electronic conductivity and low coulombic efficiency during the battery cycling process.
[0005] Meanwhile, many studies have found that the surface of silicon-oxygen compound particles has a significant impact on electrochemical stability, including the stability of the interfacial reaction between the silicon-oxygen particle surface and the electrolyte, the susceptibility to the precipitation of transition metals, etc. The above-mentioned interfacial stability significantly affects the cycle life of silicon-containing battery systems, the charge-discharge and storage stability in high-temperature environments, and the expansion of cells. Due to the existence of interfacial side reactions, a large amount of gas may be generated after the battery cell has undergone multiple charge-discharge cycles or been exposed to a high-temperature environment, resulting in safety risks. Therefore, the preparation of silicon-oxygen compound particles with stable surface properties has become one of the urgent issues in the industry.
[0006] The content of the background art is only that which is known to the applicant and does not represent prior art in the field. Summary of the Invention [Means for solving the problem]
[0007] In order to solve at least one of the above technical problems, the present invention provides a negative electrode active material comprising a negative electrode active material particle, the negative electrode active material particle comprising a silicon-based material core and a carbon film layer covering the surface of the silicon-based material core, the silicon-based material core comprising a silicon-oxygen compound; The median diameter D of the negative electrode active material 50 and the calculated particle diameter D c The ratio of D 50 / D c ≦15 and the calculated particle diameter D c = 7 × A / S, where A is the particle size distribution span value of the negative electrode active material, and S is the specific surface area of the negative electrode active material.
[0008] In some embodiments of the present invention, the median diameter D 50 and the calculated particle diameter D c The ratio of D 50 / D c ≦10, preferably D 50 / D c ≦5, more preferably D 50 / Dc Meets ≦2.5.
[0009] In some embodiments of the present invention, the specific surface area S of the negative electrode active material is 0.1 to 15 m 2 / g, preferably 0.3 to 10m 2 / g, more preferably 0.3 to 6m 2 / g.
[0010] In some embodiments of the present invention, the median diameter D 50 is 0.2 to 20 μm, preferably 1 to 15 μm, more preferably 3 to 13 μm, The particle size distribution span value A of the negative electrode active material is 2.0 or less, preferably 1.5 or less, and more preferably 1.2 or less.
[0011] In some embodiments of the present invention, the silicon based material core further comprises elemental lithium.
[0012] In some embodiments of the present invention, the content of lithium element in the negative electrode active material particles is 0.1 to 20 wt%, preferably 2 to 18 wt%, more preferably 4 to 15 wt%.
[0013] In some embodiments of the present invention, the content of silicon element in the negative electrode active material particles is 30 to 80 wt%, preferably 35 to 65 wt%, and more preferably 40 to 65 wt%.
[0014] In some embodiments of the present invention, the negative electrode active material particles further comprise silicon nanoparticles, and the median diameter of the silicon nanoparticles dispersed within the silicon-based material core is in the range of 0.1 to 35 nm, preferably 0.5 to 20 nm, and more preferably 1 to 15 nm.
[0015] In some embodiments of the present invention, the carbon film layer has a thickness of 0.001 to 5 μm, preferably 0.005 to 2 μm, and more preferably 0.01 to 1 μm.
[0016] In some embodiments of the present invention, the mass proportion of the carbon membrane layer is 0.01 to 20 wt %, preferably 0.1 to 15 wt %, more preferably 1 to 12 wt %, of the total mass of the negative electrode active material particles.
[0017] The present invention also provides an electrode comprising the above-described negative electrode active material.
[0018] The present invention also provides a battery comprising the above electrode.
[0019] The present invention relates to Providing silicon-oxygen compound particles; a step of coating the surface of the silicon-oxygen compound particles with a carbon film layer; The present invention also provides a method for preparing the negative electrode active material, comprising the steps of:
[0020] In some embodiments of the invention, the method further comprises: The method further includes the step of doping the silicon-oxygen compound particles covering the carbon membrane layer with lithium. Effect of the Invention
[0021] The negative electrode active material carbon film layer provided by the present invention has fewer defects, high interfacial stability in electrochemical systems, better cycle stability, high temperature properties, and less expansion and gas generation.
[0022] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. [Brief description of the drawings]
[0023] [Figure 1] 1 is a flow chart of a preparation process provided according to one embodiment of the present invention. [Diagram 2] 4 is a flow chart of a preparation process provided by another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] In order to better understand the technical means of the present invention and the advantages of each aspect thereof, the specific embodiments of the present invention will be described in more detail below with reference to the drawings and examples. However, the specific embodiments and examples described below are for the purpose of illustration only and are not intended to limit the present invention.
[0025] It should be noted that all similar replacements and modifications are obvious to those skilled in the art, and such replacements and modifications are deemed to be included in the present invention. Although the method and use of the present invention have been described through the preferred embodiments, it is obvious that those skilled in the art can make modifications or suitable changes and combinations to the method and use described herein to realize and use the technology of the present invention without departing from the content, spirit and scope of the present invention.
[0026] <Negative electrode active material> The present invention provides an anode active material for a battery having anode active material particles. The anode active material particles include a silicon-based material core and a carbon film layer covering the surface of the silicon-based material core. The silicon-based material core includes a silicon-oxygen compound. The silicon-based material core can be a silicon-oxygen compound particle or a lithium-intercalated silicon-oxygen compound particle, i.e., the silicon-based material core can include a lithium element.
[0027] The median diameter D of the negative electrode active material provided by the present invention 50 and the calculated particle diameter D c The ratio of D 50 / D c ≦15 and the calculated particle size D c = 7 × A / S, where A is the particle size distribution span value of the negative electrode active material, and S is the specific surface area of the negative electrode active material. 90 -D 10 ) / D 50 , where particle diameter D 10 is the particle size at which the cumulative distribution of particles is 10%, i.e., the volume content of particles smaller than this particle size accounts for 10% of the total particles, and the median diameter D 50is the particle size at which the cumulative distribution of particles is 50%, i.e., 50% of the particles are above this value and 50% of the particles are below this value, and the particle size D 90 is the particle size at which the cumulative distribution of particles is 90%, i.e., the volume content of particles smaller than this particle size accounts for 90% of the total particles.
[0028] As a result of their research, the inventors have found that the surface characteristics of negative electrode active material particles used in batteries, particularly the interfacial stability in an electrochemical system, are closely related to the structure of the carbon film layer that coats the surface of the particles.
[0029] Common structural defects of the carbon film layer include pores in the carbon film layer, impurities, disorder of the crystal structure of the carbon layer, many bonds of hydrocarbons / carbon-oxygen / carbon-sulfur, many surface wrinkles, cracks, etc. The above structural defects may increase the specific surface area of the negative electrode active material, increase side reactions with the electrolyte, and cause stronger interactions with transition metals eluted from the positive electrode, which may deteriorate the electrochemical properties of the negative electrode active material, such as cycle stability, high temperature stability, and expansion rate. Due to the existence of interfacial side reactions, the battery cell may experience significant expansion and gas generation after cycling or high temperature environment, which may cause safety risks.
[0030] The median diameter D of the negative electrode active material provided by the present invention 50 and the calculated particle diameter D c The ratio of D 50 / D c When it satisfies ≦15, the carbon film layer has fewer defects, so that the interface stability in the electrochemical system is high, the cycle stability is better, the high temperature properties are better, and the expansion and gas generation are less.
[0031] In some embodiments of the present invention, D 50 / D c ≦10, preferably D 50 / D c ≦5, more preferably D 50 / D c ≦2.5. The smaller this value is, the fewer the defects in the carbon film layer on the surface of the negative electrode active material are.
[0032] In some embodiments of the present invention, the specific surface area S of the negative electrode active material is 0.1 to 15 m 2 / g, preferably 0.3 to 10m 2 / g, more preferably 0.3 to 6m 2 / g.
[0033] In some embodiments of the present invention, the median diameter D of the negative electrode active material 50 is 0.2 to 20 μm, preferably 1 to 15 μm, and more preferably 3 to 13 μm.
[0034] In some embodiments of the present invention, the particle size distribution span value A of the negative electrode active material is 2.0 or less, preferably 1.5 or less, and more preferably 1.2 or less.
[0035] In some embodiments of the present invention, the content of silicon element in the negative electrode active material particles can be 30-80 wt%, preferably 35-65 wt%, more preferably 40-65 wt%, so that the material has a very high reversible capacity.
[0036] In some embodiments of the present invention, the content of lithium element in the silicon-based material core may be 0.1-20 wt%, preferably 2-18 wt%, more preferably 4-15 wt%.
[0037] In some embodiments of the present invention, the negative electrode active material particles also contain nanosilicon elements that can be uniformly dispersed in the silicon-based material core. The nanosilicon elements can be present in the silicon-based material core in the form of nanoparticles, and can have a median diameter in the range of 0.1 to 35 nm, preferably 0.5 to 20 nm, and more preferably 1 to 15 nm. Particles within this particle size range have small particle expansion and are unlikely to burst when lithium ions are repeatedly inserted and removed, so that lithium ion secondary batteries using this material have small cycle expansion and can achieve stable cycles.
[0038] In some embodiments of the present invention, the thickness of the carbon film layer is 0.001-5 μm, preferably 0.005-2 μm, more preferably 0.01-1 μm. The presence of the carbon film layer effectively improves the electrical conductivity of the particles, reduces the contact resistance between the particles in the negative electrode plate, and between the negative electrode plate and the current collector, thereby improving the lithium insertion / extraction efficiency of the material, reducing the polarization of the lithium ion battery, and promoting the cycle stability.
[0039] In some embodiments of the present invention, the mass proportion of the carbon membrane layer may be 0.01 to 20 wt %, preferably 0.1 to 15 wt %, and more preferably 1 to 12 wt % of the total mass of the negative electrode active material particles.
[0040] The negative electrode active material for a battery provided in the present application has relatively stable surface properties, and therefore has high interfacial stability with the electrolyte and little interaction with transition metals precipitated from the positive electrode. A battery prepared using the negative electrode active material has the advantages of excellent cycle stability, high-temperature properties, small expansion, and small gas generation.
[0041] <Method of preparing negative electrode active material> FIG. 1 is a flow chart showing the steps of preparing a negative electrode active material according to an exemplary embodiment of the present invention.
[0042] S101: Silicon-oxygen compound particles are prepared.
[0043] The specific preparation process can be carried out in the following steps: First, a mixture of metal silicon powder and silicon dioxide powder is heated in the temperature range of 900°C to 1600°C under an inert gas atmosphere or reduced pressure conditions to generate silicon oxide gas. The molar ratio of metal silicon powder to silicon dioxide powder is set in the range of 0.5 to 1.5. Gas generated by the thermal reaction of the raw materials is deposited on an adsorption plate. When the temperature inside the reactor falls below 100°C, the deposit is removed and crushed and powdered using equipment such as a ball mill or jet mill to obtain silicon-oxygen compound particles.
[0044] The silicon-oxygen compound particles in the present invention include silicon oxide (silicon monoxide and / or silicon dioxide) materials. In an exemplary embodiment of the present invention, the stoichiometric ratio of silicon oxide in the silicon oxide compound particles can be 1:0.4-1:2, alternatively 1:0.6-1:1.5, and further alternatively 1:0.8-1:1.2. Of course, in addition to silicon and oxygen, other trace impurity elements may be included.
[0045] S102: The surface of the silicon-oxygen compound particles is coated with a carbon film layer.
[0046] The structure of the carbon film layer on the particle surface is closely related to its preparation process, and the carbon film layers obtained under different process parameters (e.g., type of carbon source, coating temperature, atmosphere, air pressure, heating rate, carbon content, magnetic field, electric field, etc.) and different furnace structure designs have significant differences in structure and also have significantly different degrees of defects.
[0047] According to an exemplary embodiment, the silicon-oxygen compound may be a silicon oxide compound that is not disproportionated, or may be a silicon-oxygen compound that has been subjected to a disproportionation heat treatment. The temperature of the disproportionation heat treatment may be 600-1100°C, alternatively 700-1000°C, and more preferably 800-1000°C.
[0048] In the present invention, the carbon film layer can be directly obtained by chemical vapor deposition (CVD). The carbon source used in CVD is a hydrocarbon compound gas, and the decomposition temperature of the hydrocarbon compound gas can be 600 to 1100°C, preferably 700 to 1000°C, and more preferably 800 to 1000°C. In the above-mentioned carbon film coating process, the selection of the carbon source, the carbonization temperature, the amount of the carbon source added, the gas ratio and flow rate, etc. have a significant effect on the final carbon film structure. In addition, the structure of the carbon film is also significantly affected by the control of the air pressure (vacuum degree) and atmosphere ratio during the carbon film growth process, and the unique design of the air flow direction. Preferably, a mixture of a carbon source gas and an inert gas or a reducing gas (argon, nitrogen, helium, hydrogen, etc.) is introduced at a certain ratio, and the quality of the obtained carbon film is superior to that of the one that only pure carbon source gas is introduced. Furthermore, controlling the volume ratio of the carbon source gas in the mixed gas to 90% or less, preferably 75% or less, and more preferably 65% or less, helps to obtain a carbon film layer with better coating quality and uniformity. In addition, by lowering the gas pressure inside the furnace during the carbon film growth process and maintaining a certain degree of negative pressure (vacuum), the uniformity of the carbon film layer can be significantly improved, resulting in a carbon film layer that is smoother and denser.
[0049] The carbon membrane layer can also be obtained by a method in which carbon reactive coating is performed first, followed by heat treatment and carbonization in a non-oxidizing atmosphere. In the carbon reactive coating method, any of a mechanical melter, a VC mixer, a coating kettle, a spray dryer, a sand mill, or a high-speed disperser can be used. The solvent used in coating is one or more combinations of water, methanol, ethanol, isopropyl alcohol, n-butanol, ethylene glycol, ether, acetone, N-methylpyrrolidone, methylbutanone, tetrahydrofuran, benzene, toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, and chloroform. The carbon source may be one or more combinations of coal pitch, petroleum pitch, polyvinyl alcohol, epoxy resin, polyacrylonitrile, polymethyl methacrylate, glucose, sucrose, polyacrylic acid, and polyvinylpyrrolidone. The equipment used for heat treatment and carbonization can be any of a rotary furnace, a ladle refining furnace, a roller hearth kiln, a pusher kiln, an atmospheric box furnace, and a tubular furnace. The temperature of the heat treatment and carbonization may be 600-1100°C, preferably 700-1000°C, more preferably 800-1000°C, and the holding time is 0.5-24 hours. The non-oxidizing atmosphere may be provided by at least one gas of nitrogen, argon, hydrogen, or helium. In the above carbon film coating process, the selection of the carbon source, the carbonization temperature, the amount of the carbon source added, the heating rate, the design of the heating and temperature holding procedure, the strength of the mechanical stirring, and the selection of the coating device all have a significant effect on the final carbon film structure. Preferably, the design of the heating procedure with multi-stage temperature holding helps to obtain a carbon film coating structure with better quality. The selection of an appropriate intermediate temperature holding procedure helps to obtain a more uniform and dense carbon coating layer by sufficiently melting the carbon source compound, obtaining appropriate fluidity, and carrying out a preliminary decoking reaction. In addition, in the heat treatment and carbonization process, dynamic carbonization is preferred in which the material is dynamically stirred during the temperature increase and temperature maintenance processes, which promotes effective discharge of volatile matter in the carbonization process of the carbon source and helps to obtain a carbon film with a denser structure and fewer defects.
[0050] 2 is a flow chart showing a process for preparing a negative electrode active material according to another exemplary embodiment of the present invention, comprising the steps of: S201: A step of preparing silicon-oxygen compound particles. S202: A process for coating the surface of silicon-oxygen compound particles with a carbon film layer. S203: Doping the silicon-oxygen compound particles coated with a carbon film layer with lithium.
[0051] In the present invention, the doping (insertion of lithium element) of silicon-oxygen compound particles can be performed by electrochemical doping, liquid phase doping, thermal doping, etc. The doping atmosphere of lithium element is a non-oxidizing atmosphere, and the non-oxidizing atmosphere is at least one of nitrogen, argon, hydrogen, and helium.
[0052] The methods for inserting lithium element (lithium doping modification method) include the following.
[0053] 1) Electrochemical methods An electrochemical cell including four components, a tank, an anode electrode, a cathode electrode, and a power source, is prepared, and the anode electrode and the cathode electrode are connected to both ends of the power source, respectively. At the same time, the anode electrode is connected to a lithium source, and the cathode electrode is connected to a container having silicon-oxygen compound particles. An organic solvent is filled in the tank, and the lithium source (anode electrode) and the container having silicon-oxygen compound particles (cathode electrode) are immersed in the organic solvent. After passing a current, an electrochemical reaction occurs, and lithium ions are inserted into the structure of the silicon-oxygen compound, resulting in lithium-doped modified silicon-oxygen compound particles. Examples of the organic solvent include ethylene carbonate, propylene carbonate, butylene carbonate, fluorinated ethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, propyl acetate, propionic acid ethyl ester, propyl propionate, dimethyl sulfoxide, and the like. The organic solvent also contains an electrolyte lithium salt, and lithium hexafluorophosphate (LiPF6), lithium hexafluorophosphate (LiBF4), lithium perchlorate (LiClO4), etc. can be used. The lithium source (anode electrode) can be a lithium foil, or a lithium compound such as lithium carbonate, lithium oxide, lithium hydroxide, lithium cobalt oxide, lithium iron phosphate, lithium manganate, lithium vanadium phosphate, or lithium nickel oxide.
[0054] 2) Liquid phase doping method Metallic lithium, an electron transfer catalyst, and silicon-oxygen compound particles are added to an ether-based solvent, and the mixture is stirred and heated under a non-oxidizing atmosphere, and the constant temperature reaction is maintained until the metallic lithium in the solution is completely disappeared. Due to the action of the electron transfer catalyst, metallic lithium dissolves in the ether-based solvent and forms a lithium ion coordination compound with a low reduction potential, which reacts with the silicon-oxygen compound, and the lithium ion can enter the structure of the silicon-oxygen compound. Examples of the electron transfer catalyst include biphenyl and naphthalene. Examples of the ether-based solvent include methyl butyl ether, ethylene glycol butyl ether, tetrahydrofuran, and ethylene glycol dimethyl ether. The temperature of the constant temperature reaction is 25 to 200°C. The non-oxidizing atmosphere is provided by at least one gas of nitrogen, argon, hydrogen, or helium.
[0055] 3) Thermal doping method The silicon-oxygen compound particles and the lithium-containing compound are uniformly mixed, and then heat-treated in a non-oxidizing atmosphere. Examples of the lithium-containing compound include lithium hydroxide, lithium carbonate, lithium oxide, lithium peroxide, lithium hydride, lithium nitrate, lithium acetate, and lithium oxalate. As the mixing method, any of a high-speed disperser, a high-speed stirring mill, a ball mill, a conical mixer, a spiral mixer, a stirring mixer, and a VC mixer is adopted. The equipment used for the heat treatment is any of a rotary furnace, a ladle refining furnace, a liner furnace, a roller hearth kiln, a pusher kiln, an atmospheric box furnace, and a tubular furnace. The temperature of the heat treatment is 400 to 850°C, preferably 550 to 800°C, the retention time is 1 to 12 hours, and the heating rate is more than 0.1°C / min and 10°C / min or less. The non-oxidizing atmosphere is provided by at least one gas of nitrogen, argon, hydrogen, or helium.
[0056] The lithium element insertion process is carried out after coating the carbon membrane layer, which can inhibit the silicon grain growth in the silicon-oxygen compound during heat treatment. This allows the nanoscale silicon single particles to be uniformly dispersed and fixed in the matrix of the lithium silicate compound or silicon-oxygen compound, effectively inhibiting the expansion of silicon nanoparticles and preventing the silicon particles from gradually coalescing into larger particles during the charge and discharge process, thereby reducing the expansion and deformation of the battery during the cycle process, reducing the electrical failure of the silicon material, and realizing a small cycle expansion and stable cycle of the lithium ion secondary battery using this material. In addition, the carbon membrane layer coating process is carried out before the lithium element is inserted, which helps to obtain a carbon membrane layer with better quality and more complete coverage.
[0057] At the same time, the lithium element insertion process affects the structure of the carbon film layer on the surface of the silicon-oxygen compound particles to different degrees: when the diffusion process is gentle and controllable, the impact on the carbon film layer structure on the particle surface is minor, and when the impact on the diffusion process is relatively intense, it may cause changes in the carbon film layer structure.
[0058] <Method for evaluating the characteristics of negative electrode active materials> 1. Material measurement: The negative electrode active materials prepared in each example and comparative example are evaluated for their characteristics using the following equipment. A BetterSize 2000 laser particle size distribution meter (manufactured by Dandong Baitec Co., Ltd.) is used to measure the particle size distribution of the negative electrode active material. A scanning electron microscope (SEM) (manufactured by Hitachi, SU8010) is used to observe the surface morphology of the negative electrode active material. A specific surface area measuring instrument (manufactured by Quantum Chrome Instruments, NOVA 4200e) is used to measure the specific surface area of the negative electrode active material. The requirements for measuring the specific surface area are as follows: A sample is weighed into a sample tube, and the specific surface area of the sample is measured by a multipoint method using nitrogen gas and a relative pressure p / p0=0.05-0.3.
[0059] 2. Preparation of uniform slurry and electrode plate: 30 parts of the above-mentioned negative electrode active material, 64 parts of artificial graphite, 2.5 parts of conductive additive, and 3.5 parts of binder are taken and made into an aqueous slurry, which is then applied, dried, and rolled to obtain a negative electrode plate containing the negative electrode active material of the present application.
[0060] 3. Full cell evaluation: The negative electrode plate obtained from the negative electrode active material prepared in each Example and Comparative Example was cut, vacuum baked, rolled with a pair of ternary positive electrode plate and separator, packed into an aluminum plastic shell of a corresponding size, injected with a certain amount of electrolyte, degassed and sealed, and a lithium ion battery of about 3.2 Ah was obtained after formation. This full cell was subjected to a 60-day fully charged storage test at 60°C to test the thermal expansion coefficient, capacity retention rate, and capacity recovery rate of the system after high-temperature fully charged storage, and was used to evaluate the stability of the system at high temperature storage. The thermal expansion coefficient test method is to take out the battery cell after storing it at 60°C for 60 days in a fully charged state, and immediately test the thickness of the battery cell as d, where the thickness of the battery cell in the initial half-charged state is d0, and the thermal expansion coefficient = (d-d0) / d0. Next, after cooling the battery cell, a discharge test is performed in a battery testing system manufactured by NEWARE, and the discharge capacity is D1, the discharge capacity of the battery cell before high-temperature storage is D0, and the capacity maintenance rate = D1 / D0. Then, one charge / discharge cycle is performed on the battery cell, and the discharge capacity is D2, and the capacity recovery rate = D2 / D0.
[0061] The present application will now be further described with reference to specific examples.
[0062] (Example 1-1) 1000g of silicon-oxygen compound particles with a median diameter of 6μm (silicon:oxygen atomic ratio 1:1) and low-temperature coal pitch powder were mixed uniformly in a coating kettle by a dry method, and then 2000g of dimethylformamide was added while stirring to uniformly disperse the mixed powder in the dimethylformamide. The coating kettle was then heated to 340°C and held at a constant temperature for 3 hours to obtain a silicon-oxygen compound material coated with coal pitch. The material was statically heated to 680°C under a nitrogen gas atmosphere and held for 4 hours to carbonize the coal pitch. After cooling, the material obtained was sieved through a 500 mesh sieve to obtain a silicon-oxygen compound powder coated with a carbon film. The carbon content of the silicon-oxygen compound powder coated with a carbon film was measured to find that it was 7wt%.
[0063] The specific surface area of the negative electrode active material obtained in the above process is S = 15 m 2 / g, median diameter of product D 50 The particle size distribution span value A is 1.52, and the particle diameter D calculated from the specific surface area is 10.64 μm. c = 0.71 μm, so the median diameter D 50 and the calculated particle diameter D c The ratio was 15.
[0064] 30 parts of the negative electrode active material, 64 parts of artificial graphite, 3.5 parts of conductive agent, and 2.5 parts of binder were mixed and coated in an aqueous slurry form, which was then dried and rolled to obtain a silicon-containing negative electrode plate.
[0065] In this embodiment, the results of high-temperature storage evaluation of a full cell containing the negative electrode active material were as follows: after being stored at 60° C. for 60 days in a fully charged state, the thermal expansion coefficient of the battery cell was 22.7%, air bubbles were present in the battery cell, the capacity retention rate after high-temperature storage was 78.6%, and the capacity recovery rate was 86.3%.
[0066] (Example 1-2) The process was the same as in Example 1-1, except that the carbonization temperature of the coal pitch was adjusted to 780°C, and the carbon content was still 7wt%.
[0067] The performance parameters are shown in Table 1.
[0068] (Examples 1-3) 1000g of silicon-oxygen compound particles with a median diameter of 9μm and medium-temperature coal pitch powder were mixed uniformly in a VC reactor by dry method, then directly heated to 720℃, held at a constant temperature and stirred for 4 hours to carbonize the coal pitch in situ. After cooling, the resulting material was sieved through a 500 mesh sieve to obtain a silicon-oxygen compound powder coated with a carbon film. The carbon content of the silicon-oxygen compound powder coated with a carbon film was measured and found to be 7wt%.
[0069] Table 1 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0070] (Examples 1 to 4) 1000g of silicon-oxygen compound particles with a median diameter of 8μm and high-temperature coal pitch powder were mixed uniformly in a VC reactor by dry method, then heated to 450℃ and stirred at a constant temperature for 3 hours to give the coal pitch sufficient fluidity and achieve uniform coating, then heated to 780℃ and held for 5 hours for carbonization, maintaining sufficient stirring during the carbonization process to promote effective discharge of volatile matter during the pitch carbonization process, thereby obtaining a carbon membrane layer with a denser structure. After cooling, the material obtained was sieved through a 500 mesh sieve to obtain a silicon-oxygen compound powder coated with a carbon membrane. The carbon content of the silicon-oxygen compound powder coated with a carbon membrane was measured and found to be 6wt%.
[0071] Table 1 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0072] (Examples 1 to 5) 1000g of silicon-oxygen compound particles with a median diameter of 7μm were weighed out and placed in a CVD furnace. Using methane as the carbon source, a coating reaction was carried out at 800℃ with a methane to argon flow ratio of 1:1, resulting in silicon-oxygen compound particles coated with a carbon film layer. The carbon content of the silicon-oxygen compound powder coated with the carbon film was measured and found to be 5wt%.
[0073] Table 1 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0074] (Examples 1 to 6) 1000g of silicon-oxygen compound particles with a median diameter of 10μm were weighed out and placed in a CVD furnace. Using methane as the carbon source, a coating reaction was carried out at 800℃ with a methane to argon flow ratio of 2:1, resulting in silicon-oxygen compound particles coated with a carbon film layer. The carbon content of the silicon-oxygen compound powder coated with the carbon film was measured and found to be 7wt%.
[0075] Table 1 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0076] (Examples 1 to 7) 1000g of silicon-oxygen compound particles with a median diameter of 6μm were weighed out and placed in a CVD furnace. Using methane as the carbon source, a low-pressure coating reaction was carried out at 800℃ with a methane to argon flow ratio of 2:1. Although the low-pressure CVD reaction has low production efficiency, it can significantly improve the uniformity of the carbon film layer, resulting in a carbon film layer that is smoother, denser, and has fewer defects. The carbon content of the silicon-oxygen compound powder coated with the carbon film was measured and found to be 7wt%.
[0077] Table 1 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0078] (Examples 1 to 8) 1000g of silicon-oxygen compound particles with a median diameter of 5μm were weighed out and placed in a CVD furnace. Using methane as the carbon source, a coating reaction was carried out at 800℃ with a methane to argon flow ratio of 0.6:1, yielding silicon-oxygen compound particles coated with a carbon film layer. The carbon content of the silicon-oxygen compound powder coated with the carbon film was measured and found to be 6wt%.
[0079] Table 1 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0080] (Examples 1-9 to 1-17) As in Examples 1-1 to 1-8, silicon-oxygen compound particles were used as the raw material, and different carbon film-coated silicon-oxygen compound powders in Examples 1-9 to 1-17 were obtained using different carbon film coating processes, including adjustments to the selection of carbon source, carbonization temperature, amount of carbon source added, air pressure (vacuum level), atmosphere ratio, air flow direction, as well as the temperature rise rate, design of temperature rise and temperature holding procedures, strength of mechanical stirring, and selection of equipment.
[0081] Table 1 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0082] (Comparative Example 1-1) 1000g of silicon-oxygen compound particles and sucrose were mixed uniformly in a coating kettle by a dry method, then heated to 200°C and stirred at a constant temperature for 3 hours, then further heated to 500°C and held for 5 hours for carbonization. After cooling, the material obtained was sieved through a 500 mesh sieve to obtain a silicon-oxygen compound powder coated with a carbon film. The carbon content of the silicon-oxygen compound powder coated with a carbon film was measured and found to be 10wt%.
[0083] Table 1 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0084] (Comparative Example 1-2) 1000g of silicon-oxygen compound particles and sucrose were mixed uniformly in a coating kettle by dry method, then heated to 180℃ and stirred at a constant temperature for 3 hours, then further heated to 400℃ and held for 8 hours for carbonization. After cooling, the material obtained was sieved through a 500 mesh sieve to obtain silicon-oxygen compound powder coated with a carbon film. The carbon content of the silicon-oxygen compound powder coated with a carbon film was measured and found to be 8wt%.
[0085] Table 1 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0086] [Table 1] JPEG2025508921000003.jpg80169
[0087] As can be seen from Table 1, the median diameter D 50 and the calculated particle diameter D c Ratio of D 50 / D c The smaller the value, the better the high temperature stability of the negative electrode active material, the smaller the expansion, and the lower the possibility of gas generation.
[0088] Furthermore, as can be seen from Table 1, the carbon film layers obtained under different process parameters (type of carbon source, coating temperature, atmosphere, air pressure, heating rate, carbon content, heating and temperature holding procedure, mechanical stirring, etc.) and different furnace structure designs have significant differences in structure and also obviously different degrees of defects.
[0089] (Example 2-1) Using the negative electrode active material of Example 1-16 as the raw material, the powder, metallic lithium ribbon and biphenyl were placed in a sealable glass container, and then methyl butyl ether was added and stirred under an argon gas atmosphere to react. After the reaction was completed and the powder was dried, it was placed in an argon atmosphere and subjected to heat treatment, heated to 680°C at a heating rate of 2°C per minute, held for 10 hours, and naturally cooled to obtain a lithium-doped silicon-oxygen compound powder.
[0090] Table 2 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0091] (Example 2-2)
[0092] The product of Example 1-16 was used as the raw material, and the procedure was the same as Example 2-1, except that the heat treatment process after lithium doping was changed as follows: the temperature was raised to 720°C at a rate of 5°C per minute, and then the temperature was maintained for 3 hours. After natural cooling, a lithium-doped silicon-oxygen compound powder was obtained.
[0093] Table 2 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0094] (Example 2-3) The product of Example 1-16 was used as the raw material, and the procedure was the same as Example 2-1, except that the heat treatment process after lithium doping was changed as follows: the temperature was raised to 720°C at a rate of 10°C per minute, and then the temperature was maintained for 6 hours. After natural cooling, a lithium-doped silicon-oxygen compound powder was obtained.
[0095] Table 2 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0096] (Examples 2-4) The product of Example 1-16 was used as the raw material, and the procedure was the same as Example 2-1, except that the heat treatment process after lithium doping was changed as follows: the temperature was raised to 850°C at a rate of 10°C per minute, and then the temperature was maintained for 2 hours. After natural cooling, a lithium-doped silicon-oxygen compound powder was obtained.
[0097] Table 2 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0098] (Examples 2-5) Using the product of Examples 1-10 as the raw material, the above particles were mixed with a lithium-containing compound (lithium oxide, lithium hydride, lithium hydroxide, lithium carbonate, etc.), and the mixed powder was placed in an argon atmosphere and subjected to heat treatment. The temperature was increased to 400°C at a rate of 2°C per minute and held for 3 hours, and then further increased to 650°C and held for 10 hours. After natural cooling, a lithium-containing silicon-oxygen compound powder covered with a carbon film was obtained.
[0099] Table 2 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0100] (Examples 2-6) The product of Example 1-10 was used as the raw material, and the same procedure as Example 2-5 was followed, except that the heat treatment process after lithium doping was changed as follows: the temperature was directly raised to 700°C at a rate of 5°C per minute, and then the temperature was maintained for 6 hours. After natural cooling, a lithium-doped silicon-oxygen compound powder was obtained.
[0101] Table 2 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0102] (Examples 2-7) The product of Example 1-10 was used as the raw material, and the same procedure as Example 2-5 was followed, except that the heat treatment process after lithium doping was changed as follows: the temperature was directly raised to 820°C at a rate of 10°C per minute, and then the temperature was maintained for 2 hours. After natural cooling, a lithium-doped silicon-oxygen compound powder was obtained.
[0103] Table 2 shows the performance parameters and high-temperature storage characteristics of a battery cell using this negative electrode active material.
[0104] [Table 2]
[0105] Combining the data in Tables 1 and 2, the lithium element insertion process affects the structure of the carbon film layer on the surface of silicon-oxygen compound particles to different degrees. When the diffusion process is gentle and controllable, the impact on the carbon film layer structure on the particle surface is slight; when the diffusion process is relatively severe, it causes the carbon film layer structure to change, reducing the interface stability of the material, which leads to the deterioration of the high-temperature storage properties of the battery using the negative active material and the increase in swelling.
[0106] The above examples are merely examples for clarifying the present invention, and are not intended to be limiting to the embodiments. Those skilled in the art can make various changes or modifications based on the above description. It is not necessary to list all the embodiments here. However, obvious changes or modifications derived therefrom still fall within the protection scope of the present invention.
Claims
1. A negative electrode active material comprising a negative electrode active material particle, the negative electrode active material particle comprising a silicon-based material core and a carbon film layer covering a surface of the silicon-based material core, the silicon-based material core comprising a silicon-oxygen compound; The median diameter D of the negative electrode active material 50 The calculated particle diameter D c The ratio of D 50 / D c ≦15, and the calculated particle diameter D c = 7 × A / S, where A is the particle size distribution span value of the negative electrode active material, and S is the specific surface area of the negative electrode active material. A negative electrode active material comprising:
2. The median diameter D of the negative electrode active material 50 The calculated particle diameter D c The ratio of D 50 / D c ≦10, preferably D 50 / D c ≦5, more preferably D 50 / D c The negative electrode active material according to claim 1 , wherein the negative electrode active material satisfies a condition of ≦2.
5.
3. The specific surface area S of the negative electrode active material is 0.1 to 15 m 2 / g, preferably 0.3 to 10 m 2 / g, more preferably 0.3 to 6m 2 The negative electrode active material according to claim 1 , wherein the molecular weight of the negative electrode active material is 1000 or more.
4. The median diameter D of the negative electrode active material 50 is 0.2 to 20 μm, preferably 1 to 15 μm, more preferably 3 to 13 μm, The particle size distribution span value A of the negative electrode active material is 2.0 or less, preferably 1.5 or less, and more preferably 1.2 or less. The negative electrode active material according to claim 1 .
5. The negative electrode active material according to claim 1 , wherein the silicon-based material core further comprises a lithium element.
6. The negative electrode active material according to claim 5, wherein the content of lithium element in the negative electrode active material particles is 0.1 to 20 wt%, preferably 2 to 18 wt%, more preferably 4 to 15 wt%.
7. 2. The negative electrode active material according to claim 1, wherein the content of silicon element in the negative electrode active material particles is 30 to 80 wt%, preferably 35 to 65 wt%, more preferably 40 to 65 wt%.
8. The negative electrode active material according to claim 1, characterized in that the negative electrode active material particles further comprise silicon elemental nanoparticles, and the median diameter of the silicon elemental nanoparticles dispersed within the silicon-based material core is in the range of 0.1 to 35 nm, preferably 0.5 to 20 nm, and more preferably 1 to 15 nm.
9. 2. The negative electrode active material according to claim 1, wherein the carbon film layer has a thickness of 0.001 to 5 μm, preferably 0.005 to 2 μm, and more preferably 0.01 to 1 μm.
10. The negative electrode active material according to claim 1, wherein the mass ratio of the carbon membrane layer is 0.01 to 20 wt %, preferably 0.1 to 15 wt %, more preferably 1 to 12 wt % of the total mass of the negative electrode active material particles.
11. An electrode, comprising the negative electrode active material according to any one of claims 1 to 10.
12. A battery, characterized in that it comprises an electrode according to claim 11.
13. A method for preparing the negative electrode active material according to claim 1, comprising the steps of: Providing silicon-oxygen compound particles; coating the surface of the silicon-oxygen compound particles with a carbon film layer; A method comprising:
14. 14. The method of claim 13, further comprising the step of doping the silicon-oxygen compound particles covering the carbon membrane layer with lithium.
Citation Information
Patent Citations
Negative electrode material for secondary battery with non-aqueous electrolyte, method for manufacturing negative electrode material for secondary battery with non-aqueous elctrolyte, and lithium ion secondary battery
CN102214824A
Silicon-silicon composite oxide-carbon composite, method for preparing same, and negative electrode active material comprising same
WO2021149996A1